2019
DOI: 10.1111/vop.12647
|View full text |Cite
|
Sign up to set email alerts
|

Ocular dermoids in dogs: A retrospective study

Abstract: Objective To describe clinical features of dogs diagnosed with ocular dermoids at two veterinary teaching hospitals. Animals studied Retrospective case series of 44 dogs (49 dermoids) with ocular dermoids. Procedures Medical records of dogs evaluated by the Cornell University and University of Pennsylvania ophthalmology services were evaluated to identify dogs with a clinical diagnosis of ocular dermoids between 2004 and 2018, and 2011 and 2018, respectively. Signalment, historical, and clinical details were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 32 publications
1
13
0
5
Order By: Relevance
“…Further studies are required to determine whether ocular dermoids in French Bulldogs have an hereditary nature or this result is biased due to the popularity of this breed in our country. The majority of ocular dermoids observed in this study were conjunctival, whereas corneal and limbal were the most common locations of ocular dermoids in previous reports 89,90 . None of the locations seems to be associated with a higher incidence of secondary ocular lesions, with nonpigmented keratitis being the most frequently identified complication in our study group.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Further studies are required to determine whether ocular dermoids in French Bulldogs have an hereditary nature or this result is biased due to the popularity of this breed in our country. The majority of ocular dermoids observed in this study were conjunctival, whereas corneal and limbal were the most common locations of ocular dermoids in previous reports 89,90 . None of the locations seems to be associated with a higher incidence of secondary ocular lesions, with nonpigmented keratitis being the most frequently identified complication in our study group.…”
Section: Discussionsupporting
confidence: 44%
“…Concurrent congenital ocular malformations have been identified in previous studies, such as persistent pupillary membranes 89–91 . Nevertheless, in this study, all ocular dermoids were observed as a solo abnormality.…”
Section: Discussionmentioning
confidence: 99%
“…Podem se desenvolver em vários locais, incluindo pálpebras, conjuntiva, córnea e membrana nictitante (Badanes & Ledbetter, 2019). Os cães relatados apresentaram o dermóide na região do limbo temporal, com extensões para a córnea e conjuntiva, corroborando com os locais mais observados em cães (Badanes & Ledbetter, 2019;Erdikmen et al, 2013).…”
Section: Discussionunclassified
“…Podem manifestar clinicamente pelas massas localizadas semelhantes a pele e presença de pêlos. Embora sejam uma condição presente no nascimento do animal, os dermóides muitas vezes são reportados, quando desenvolvem o suficiente para serem visualizados ou quando complicações secundárias se tornam aparentes (Badanes & Ledbetter, 2019).…”
unclassified
“…However, this has been reported in three dogs. 7,8,21 The link between ocular dermoids and persistent pupillary membranes remains unclear, and the presence of both was probably a coincidental finding.…”
Section: Discussionmentioning
confidence: 99%